Urban voice: uma abordagem baseada em perfil e recomendação para relatar problemas de infraestrutura urbana - Gampert, Gilberto (2016)
The technological development of recent decades has provided significant changes in people's lives, especially when technological solutions for different types of problems are presented to society, improving the quality of life of people living in large urban centers. In this context, the concept of smart cities becomes an important tool for the implementation of technological resources that aim to minimize problems in several areas, such as urban mobility, natural disasters, public safety, cultural and artistic information, among others. For these new features are available in the daily lives of people, technologies, tools and applications have been developed to make the most functional cities. This work aims to present an approach based on profile and recommendation, developed for mobile devices, which gives opportunity to users reporting of urban infrastructure problems, monitoring the development of problem solving, as well as interaction with users who reported the same problems. The approach also includes a panel management, administered by a management entity that receives problem reports and forwards complaints to the sectors responsible for the solution. To develop the approach we use the user profile and the user's reputation as structural elements of the recommendation. Experiments in a real environment were also conducted in order to validate the functionality of the approach. The results showed that the approach fulfills its role of being a communication channel between the user and the management entity and, consequently, brings empowerment of its members.